O-31 Impact of an advance care planning program on the conformity of medical treatment at the end of life with nursing home residents' preferences: A controlled interview survey of bereaved family members. (1st September 2015) - Otten, Thomas; Woopen, Christiane; Christ, H; Schmitten, Jürgen in der
Abstract : Background: In Germany, beizeiten begleiten (bb) was the first Advance Care Planning (ACP) program to be regionally implemented and evaluated. While the ACP program resulted in a much higher proportion of residents with meaningful and valid advance directives (ADs) in the intervention nursing homes  (n/hs), its effect on the dying process has not yet been evaluated. Aim: To study whether bb has improved conformity of end-of-life (EOL) care with the respective person's treatment preferences. Methods: Prospective controlled survey of bereaved family members in two intervention n/hs compared with two matched controls. Using the After-death Bereaved Family Member Interview, we conducted telephone-interviews with next of kin of recently deceased residents. Results: 45 interviews in the intervention group (IG) were compared with 61 in the control group (CG; response rate 56.3% vs. 82.4%, p = 0.165). Conformity of EOL medical treatment with residents' preferences (primary endpoint), measured on a 10-point Likert scale, was significantly higher in the IG (8.67) than in the CG (7.93, p = 0.026), and relatives were more comfortable that the resident could die the way he or she wanted (9.20 vs. 8.36, p = 0.037). Advance directives were more frequent in the IG (84.4% vs. 47.5%, p < 0.001). Of the remaining 52 survey items, 7 vs. 0 showed a significant and 38 vs. 7 a numeric advantage for the IG. Discussion: This comparison indicates better conformity of EOL care with patient and family wishes in 2 n/hs practising the ACP program beizeiten begleiten versus 2 matched control n/hs.